Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.7150/ijbs.18834
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HSP90-HDAC6 Regulating Network Implicates Precision Treatment of Breast Cancer

Abstract: Breast cancer is the leading cause of women death. Heat shock protein 90 (HSP90) and Histone deacetylase 6 (HDAC6) are promising anti-cancer drug targets. However, it's still unclear the applicability of anti-HSP90 and anti-HDAC6 strategies in precision treatment of breast cancer. In current study, we found that triple negative breast cancer (TNBC) cells, compared to T47D, an ERα+ breast cancer cell line, exhibited 7~40 times lower IC50 values, stronger cell cycle perturbation, increased cell apoptosis and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Combination inhibition of HSP90‐HDAC6 interplay has been considered as an attractive strategy and achieved preclinical progress in human leukemia and breast cancer . HDAC6 and HSP90 regulate each other reciprocally in many aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Combination inhibition of HSP90‐HDAC6 interplay has been considered as an attractive strategy and achieved preclinical progress in human leukemia and breast cancer . HDAC6 and HSP90 regulate each other reciprocally in many aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the same study showed that Niltubacin, a catalytically inactive Tubacin analogue, showed similar results, indicating the possibility of participating Tubacin properties that are unrelated to its ability to inhibit HDAC6 deacetylase activity, even at low concentrations. 33,34 Furthermore, these effects could contribute to the growth-inhibitory and anti-migratory properties of Tubacin in our study on SK-OV-3-Luc 4 T1-Luc and HAP1 cells. 31,32 We suggest to take into account this possibility when interpreting the anti-migratory properties of Tubacin at low concentrations regarding breast cancer cells and neuroblastoma in literature.…”
Section: Discussionmentioning
confidence: 79%
“…31,32 We suggest to take into account this possibility when interpreting the anti-migratory properties of Tubacin at low concentrations regarding breast cancer cells and neuroblastoma in literature. 33,34 Furthermore, these effects could contribute to the growth-inhibitory and anti-migratory properties of Tubacin in our study on SK-OV-3-Luc 4 T1-Luc and HAP1 cells. Valente et al report a tert-butylcarbamate based inhibitor of neuroblastoma cell growth at an IC 50 of 0.4-0.6 μM.…”
Section: Discussionmentioning
confidence: 79%
“…[243][244][245][246][247][248][249][250][251] Recently, the combination composed of HDAC6 and TK inhibitors was proven to be effective against breast cancer, suggesting the possible development of hybrid compounds able to interact with both targets. 252,253 Compound 56 (IC 50 FGFR1 = 2.9 nM) ( Figure 6) has been previously reported by Liu et al 254 as novel and selective second generation TKi and resulted in the starting point for the design of the first F I G U R E 6 Continued series of HDAC6/FGFR1 dual inhibitors. 255 The 56/FGFR1 cocrystal structure revealed that the N-ethyl-4phenylpiperazine moiety extended out of the solvent-exposed region.…”
Section: Dual Hdac/kinase Inhibitorsmentioning
confidence: 83%
“…However, the amplification of their expression was found in different kind of cancers such as breast, gastric, cervical, oral, or bladder cancer . Recently, the combination composed of HDAC6 and TK inhibitors was proven to be effective against breast cancer, suggesting the possible development of hybrid compounds able to interact with both targets . Compound 56 (IC 50 FGFR1 = 2.9 nM) (Figure ) has been previously reported by Liu et al as novel and selective second generation TKi and resulted in the starting point for the design of the first series of HDAC6/FGFR1 dual inhibitors .…”
Section: The Mtdl Approachmentioning
confidence: 95%